Simultaneuous dual-channel heart sound and ECG acquisition unit - Shaikh Salleh, Sheikh Hussain (Penerbit UTM, 2007)
Diagnosing heart diseases with a stethoscope and ECG are two fundamental methods because of its efficiency, simplicity and noninvasive property [1]. However it takes a skilled and experienced doctor to be able to discover the heart condition by using a stethoscope [2]. With the advancement of computer systems in terms of its reproducibility, consistency and speed, it is vital in aiding the cardiologists in diagnosing tasks. The heart sounds is produced from the mechanical actions of the heart. These mechanical pumping actions correlate with the electrical activity of the heart, that can be picked up by the ECG. The heart sounds repeat with two normal sounds, that is the first heart sound (S1) and the second heart sound (S2). However, there could be the third and fourth heart sound (S3 & S4) in some conditions. The heart sounds and ECG signals are depicted in Figure 2.1. An algorithm for automated detection of S1 and S2 for the purpose of segmentation is presented by [1]. This segmented data can be fed into neural networks for cardiac abnormalities disorders detection.